The Impact of Cyber Warfare on Indonesian Cellular Frequency Operators Based on the International Information Technology Law - Putri, Ria Wierma; Natamiharja, Rudi; Davey, Orima Melati; Sabatira, Febryani; Putri, Yunita Maya (Kertha Patrika; Vol 44 No 2 (2022)DO - 10.24843/KP.2022.v44.i02.p.02, 2022)
The Radio Frequency Spectrum is a limited Natural Resource, which in terms of its management has a strategic and economic impact on the community. These limitations require the government to make quite strict regulations in the utilization of these resources. Indonesia is one of the countries that uses frequency as the consumption of daily life. This is illustrated using communication tools for the telephone network. To avoid using license frequencies, Indonesia must adjust without national and international frequency rules, considering that Indonesia is already a member of the ITU. This situation has been realized through Law no. 24 of 2015 concerning the Table of Allocation of the Indonesian Radio Frequency Spectrum, which states that the frequency allocation in Indonesia refers to the ITU-Radio Regulations. Indonesia is currently in a state of urgency for cyber security or cyber security because of the level of cybercrime or cybercrime in Indonesia. Policy handling cybercrime is different from other crime prevention. However, unlike other crime prevention, cybersecurity requires a comprehensive thought to deal with it. Therefore, the study found two problems: (1) What are the provisions for the use of frequencies in Indonesia, (2) What are the provisions regarding the existence of cyberwarfare, and (3) How are the impacts of cyberwarfare on the frequencies of Indonesian cellular operators based on international information technology law?.